1999
DOI: 10.1046/j.1365-2605.1999.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of the seminiferous epithelium with ageing is a cause of spermatoceles?

Abstract: A spermatocele refers to the cystic accumulation of semen in the male reproductive tract. Although it is thought to be caused by narrowing of the lumen of the excurrent duct with resultant cystic dilatation of the duct, the pathogenesis of the narrowing remains unknown. In the present study, we histologically examined spontaneous spermatoceles in C3H/He mice to elucidate the pathogenesis of the lesions. Testes, efferent ducts, epididymides and vas deferens obtained from young and aged C3H/He mice were embedded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…One study showed that epithelial regression with senility was the major risk factor for deferent duct dilation and cystogenesis [22]. Thus, regression of the paraurethral duct epithelium may induce post-infection dilation of the paraurethral duct.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that epithelial regression with senility was the major risk factor for deferent duct dilation and cystogenesis [22]. Thus, regression of the paraurethral duct epithelium may induce post-infection dilation of the paraurethral duct.…”
Section: Discussionmentioning
confidence: 99%
“…Itoh et al . suggested that agglutinated immature germ cells may occlude the narrow lumen of the spermatic ducts, resulting in the formation of a spermatocele 9 …”
Section: Discussionmentioning
confidence: 99%
“…Itoh et al suggested that senile seminiferous epithelium, which is shed throughout life, deposits and accumulates in the efferent ducts, leading to efferent duct obstruction and subsequent proximal dilation. 4 Most spermatocele are less than 1 cm in diameter and are singly locular. 1 Spermatocele must be differentiated from hydrocele, varicocele, epididymal cysts, tumors, infection, or other scrotal masses.…”
Section: Discussionmentioning
confidence: 99%